Intracranial recordings reveal transient response dynamics during information maintenance in human cerebral cortex. Issue 10 (3rd July 2015) - Noy, Niv; Bickel, Stephan; Zion‐Golumbic, Elana; Harel, Michal; Golan, Tal; Davidesco, Ido; Schevon, Catherine A.; McKhann, Guy M.; Goodman, Robert R.; Schroeder, Charles E.; Mehta, Ashesh D.; Malach, Rafael
Abstract: Despite an extensive body of work, it is still not clear how short term maintenance of information is implemented in the human brain. Most prior research has focused on "working memory"—typically involving the storage of a number of items, requiring the use of a phonological loop and focused attention during the delay period between encoding and retrieval. These studies largely support a model of enhanced activity in the delay interval as the central mechanism underlying working memory. However, multi‐item working memory constitutes only a subset of storage phenomena that may occur during daily life. A common task in naturalistic situations is short term memory of a single item—for example, blindly reaching to a previously placed cup of coffee. Little is known about such single‐item, effortless, storage in the human brain. Here, we examined the dynamics of brain responses during a single‐item maintenance task, using intracranial recordings implanted for clinical purpose in patients (ECoG). Our results reveal that active electrodes were dominated by transient short latency visual and motor responses, reflected in broadband high frequency power increases in occipito‐temporal, frontal, and parietal cortex. Only a very small set of electrodes showed activity during the early part of the delay period. Interestingly, no cortical site displayed a significant activation lasting to the response time. These results suggest that single item encoding is characterized by transient high frequency ECoG responses, while the maintenance of information during the delay period may be mediated by mechanisms necessitating only low‐levels of neuronal activations. Hum Brain Mapp 36:3988–4003, 2015 . © 2015 Wiley Periodicals, Inc.